Foes, ghosts, and faces in the water: self-reflexivity in postwar fiction - Dean, A (2017)
This thesis examines the nature and value of metafictional practices in the careers of postwar novelists. Discussions of metafiction have been central to accounts of postwar literature. Where debates in the 1980s and 1990s about metafiction tended to make claims about its distinctive political and theoretical power, recent work in the study of institutions has folded metafiction into the routine operation of the literary field, and attacked previous claims to distinctive value. In this thesis I both historicize self-reflexive literary practices in the literary field, an element largely absent from the earlier scholarship, and present historically determinate claims about the value of these practices, an element I suggest is missing from the more recent work. To do so, I turn to the study of autobiography, specifically Philippe Lejeune’s concept of 'autobiographical space.' In the first chapter, I explore how J. M. Coetzee develops academic literary criticism in his fiction. In the second chapter, I examine how Janet Frame responds to both the demands of a national literature and biographical inquiry into her life. In the third chapter, I address how Philip Roth handles the relationship between the politics of identity and the postwar novel. Self-reflexive practices, I show throughout, are ways of writing that were encouraged by particular formations in the literary field and were handled by writers through more or less explicit treatments of autobiographical space. I argue, though, that while these practices can be remarkably inventive, they carry no guarantees for political, theoretical, or aesthetic value.